#USportsSoMale: Gender (In)equity in Canadian Interuniversity Varsity Sport - Robinson, Daniel; Weaving, Charlene; Spicer, Christa (Journal of Intercollegiate Sport, 2023)
Herein we examine the current state of gender (in)equity within Canadian interuniversity varsity sport (U SPORTS). In so doing, we build upon the previous work of Canada’s Centre for Sport Policy Studies at University of Toronto (see Norman et al., 2021). In our examination, we accessed all 56 U SPORTS universities’ Department of Athletics official webpages. We investigated the opportunities for women to participate as student-athletes on U SPORTS interuniversity varsity sport teams as well as opportunities for women to serve as sport leaders as their universities’ Directors of Athletics (DAs) and head coaches. Our findings suggest the current situation in Canadian universities remains bleak. We also argue that immediate attention and action is needed—by multiple potential stakeholders—for meaningful change to occur. Finally, considering these findings, we offer suggestions for moving forward and creating change.